Ciertas cuestiones sobre el εἴδωλον - Ana Bertha Nova C. (Tópicos, 2013)
Plato's Sophist presents central epistemological problems. One of the main topics of this dialogue is that the character and roll of the image -a mere copy- is a constitutive component of the sophistical pseudo-knowledge. Therefore, Plato tries to analyze the difference among Image, Identity, Sameness and Predication.